ANALISIS FRAMING: KASUS FEMISIDA DALAM MEDIA MASSA DARING KOMPAS.COM PERIODE JANUARI-OKTOBER 2025 - Ridha Ayu Andini; Sunarto Sunarto (Interaksi Online, 2026)
The mass media should be able to apply the guidelines of the journalistic code of ethics and the principle of feminist journalism in their reporting on the issue of femicide. However, in reality, there are still many news reports that are discriminative toward women. This study was conducted with the aim of describing the framing constructed by the online media Kompas.com in its reporting on the issue of femicide. It used descriptive-qualitative approach with critical paradigm and second-level agenda-setting theory, this study also employed Robert M. Entman’s framing analysis model, which involves four elements of analysis: problem definition; diagnosis of causes; moral judgment; and recommendations for solutions. Based on the analysis of 10 news articles on femicide published between January and October 2025, it was found that Kompas.com employed feminist journalism framing only to a limited extent, while predominantly relying on conventional journalism framing, including the use of clickbait tactics to generate sensationalist narration. The results showed that cases of femicide are attributed to emotional issues and conflicts in the romantic relationship between the victim and the perpetrator. However, the perpetrator’s actions tend to be justified as a response to the victim’s behavior, which is perceived as violating gender roles. This is influenced by Kompas.com’s masculine standpoint, meaning that the resulting news coverage remains shaped by patriarchal ideology.